Cognitive trajectories and mortality risk in older adults: a 9-year follow-up study - Gabriela Cabett Cipolli; Daniela de Assumpção; Ivan Aprahamian; Mallak Khalid Alzahrani; Ligiana Pires Corona; Yeda Aparecida de Oliveira Duarte; Mônica Sanches Yassuda; Qian-Li Xue (GeroScience, 2026)
Cognitive decline is a central feature of aging and a major determinant of disability and mortality. Understanding cognitive trajectories is essential for identifying individuals at risk and informing preventive strategies. In this study, we estimated transition probabilities across cognitive states and examined predictors of cognitive deficit and mortality among 1,413 community-dwelling older adults for nine years. Cognitive status was assessed at baseline and at two follow-up waves (2006, 2010, and 2015) using the Mini-Mental State Examination and categorized into four trajectories: stable, worsening, improving, or fluctuating. Transition probabilities and associated predictors were estimated using discrete-time Markov models via multinomial logistic regression, including baseline cognitive status, age, sex, frailty, multimorbidity, and depressive symptoms. During follow-up, 51.1% of participants experienced cognitive decline, 46.6% remained stable, 1.3% improved, and 1.1% fluctuated. Frailty increased the odds of both cognitive deficit (OR = 3.1; 95% CI 1.86–5.18) and mortality (OR = 4.2; 95% CI 2.66–6.69). Participants aged ≥ 80 years had higher risks of cognitive deficit (OR = 5.2; 95% CI 3.63–7.48) and death (OR = 11.9; 95% CI 8.30–17.21). Prior cognitive deficit predicted subsequent decline (OR = 7.5; 95% CI 4.77–11.77) and mortality (OR = 7.2; 95% CI 4.63–11.28), whereas female sex was associated with lower mortality risk (OR = 0.50; 95% CI 0.38–0.66). These findings indicate that cognitive decline in late life follows a progressive trajectory and highlight frailty and advanced age as key predictors of cognitive deterioration and mortality, emphasizing the importance of early identification and preventive strategies.